1999
DOI: 10.1097/00043764-199906000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Abortions Among Finnish Flight Attendants

Abstract: We conducted a retrospective cohort study to investigate whether work as a cabin attendant is related to an increased risk for spontaneous abortion. Data on female cabin crew members were linked to medical records on pregnancies. There were 1751 eligible pregnancies for the final analysis. Flight attendants who worked during early pregnancy had a slightly elevated risk of spontaneous abortion, as compared with attendants who were pregnant outside a time span of active flying (odds ratio [OR] = 1.3; 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Self-reported data on spontaneous abortion at low gestational ages are often subject to bias and are difficult to interpret, particularly if obtained in studies with low participation rates. On the other hand, a register-based Finnish cohort study found a slightly elevated risk of spontaneous abortion (18).…”
Section: Discussionmentioning
confidence: 94%
“…Self-reported data on spontaneous abortion at low gestational ages are often subject to bias and are difficult to interpret, particularly if obtained in studies with low participation rates. On the other hand, a register-based Finnish cohort study found a slightly elevated risk of spontaneous abortion (18).…”
Section: Discussionmentioning
confidence: 94%
“…Pregnancy outcome may also be compromised by circadian disruption, as shift work and frequent travel across time zones have been associated with reduced fertility and poor pregnancy outcome (95,96). Pregnant women on rotating shifts have greater risk of preterm births and lowbirth-weight infants (97).…”
Section: Reproductive Systemmentioning
confidence: 99%
“…High-LET radiation is effective at directly breaking DNA strands in biological tissue, or producing chemically active radicals in tissue that alter the cell function, both of which can lead to cancer or other adverse health effects (Wilson et al, 2003;. Studies of flight attendants have suggested adverse reproductive health outcomes (Aspholm et al, 1999;Lauria et al, 2006;Waters et al, 2000). The International Commission on Radiological Protection (ICRP) classify crews of commercial aircraft as radiation workers (ICRP, 1991).…”
Section: Introductionmentioning
confidence: 99%